A wideband circularly polarized monopole antenna with elliptic ring slot patch using characteristic mode analysis. Issue 12 (20th October 2022) - Tao, Shifei; Xu, Mengnan; Ding, Zhendong; Wu, Ziying; Wang, Hao; Wang, Yan
Abstract: This article presented a wideband circularly polarization (CP) monopole antenna with elliptic ring slot patch using characteristic mode analysis (CMA). By analyzing the characteristic modes of elliptical patch and elliptical ring patch in turn, it is found that the elliptical ring slot patch can meet the phase requirement of CP. Then, the parasitic elliptical ring slot patch is used to broaden the impedance bandwidth and polarization bandwidth of the antenna. The broadband is obtained by the modal significance (MS) analysis, and the CP is realized by analyzing the characteristic current of two modes are orthogonal and the characteristic angle (CA) close to 90°. The proposed antenna was fabricated and measured with the size of 0.59λ0  × 0.59λ0  × 0.02λ0 . The measured 3‐dB axial ratio (AR) band is from 5.3 to 9.4 GHz (55.8%), and the −10 dB impedance band is from 4.5 to 9.7 GHz (73.2%).